The sin of knowledge : ancient themes and modern variations - Ziolkowski, Theodore (Princeton University Press, 2000)
"Adam, Prometheus, and Faust - their stories were central to the formation of Western consciousness and continue to be timely cautionary tales in an age driven by information and technology. Here Theodore Ziolkowski explores how each myth represents a response on the part of ancient Hebrew, ancient Greek, and sixteenth-century Christian culture to the problem of knowledge, particularly humankind's powerful, perennial, and sometimes unethical desire for it